Comparison of Open vs Laparoscopic Cholecystectomy in patients of Cholelithiasis having Previous Abdominal Surgeries - Muhammad Umair Samee, Khalid Abaidullah, Muhammad Afzal, Maham Qammar, Ejaz Iqbal, Muhammad Furqan Sharif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Most of the surgeons in our setups perform open cholecystectomy (OC) in patients of cholelithiasis having previous abdominal surgery. This is the era of laparoscopic and robotic surgery and laparoscopic cholecystectomy (LC) should be the preferred treatment for these patients as well. Aim: To observe the effect of previous abdominal surgeries on laparoscopic cholecystectomy. Study design: Randomized, controlled and multicenter experimental study. Place and duration of study: Department of Surgery, Central Park Teaching Hospital, Lahore, Noor Hospital, Kot Radha Kishan and Bilquees Hospital, Kasur from 1st January 2020 to 31st December 2021. Methodology: Fifty eight patients were allocated into 2 groups (29 in each group) not considering age and sex. Both types of surgeries were analyzed on the basis of operating time, post-operative pain (VAS) and complications. Complications were noted i.e. wound infection, bile leakage from cystic duct/CBD injury, gut injury and per operative bleeding). Type of previous surgery was also noted. Data of conversion to open cholecystectomy from laparoscopic cholecystectomy was also recorded. Results: Mean age of patients in group A was 45.99±13.42 years while mean age of patients in group B was 41.87±14.65 years and p-value 0.105. 75.2% patients in group A were female while 82.1% patients in group B were female (p-value 0.185). Operative time in group A was 45.51±8.32 minutes while operative time in group B was 70.33±13.40 minutes (p-value 0.001). VAS score was 7.34±1.80 in group A while it was 5.24±1.93 in group B (p-value 0.001). 4 patients (13.79%) in group A developed wound infection while 1 patient (3.45%) from group B developed wound infection (p-value 0.005). Bile leakage and gut injury were not seen in any of the patient from both groups. Peroperative bleeding (more than 50ml) was seen in 2 patients of group A (6.90%) while it was seen in 8 patients of group B (27.59%) p-value 0.001. Type of previous surgeries were 24 cases were of mesh hernioplasty (41.38%), 16 cases of herniorrhaphy (27.59%), 10 laparotomies for peritonitis/intestinal obstruction (17.24%) and 8 cases of laparotomies for gynecological problems (13.79%). No case of laparoscopic cholecystectomy was converted to open cholecystectomy. Conclusion: Laparoscopic cholecystectomy is a safe and excellent option in patients of cholelithiasis having previous abdominal surgery. Even though LC takes more time due to adhesions but this issue does not out weights the benefits of laparoscopic cholecystectomy over open cholecystectomy. Keywords: Laparoscopic cholecystectomy, Cholelithiasis